The Translator’s New Clothes Translating the Dual Audience in Andersen’s “The Emperor’s New Clothes” - Van Coillie, Jan (Meta, 2008)
Abstract‘The Emperor’s New Clothes’ is one of Hans Christian Andersen’s best known fairy tales. All over the world it appeals to children and adults alike. As such it belongs to what Zohar Shavit (1986) called ‘children’s literature with an ambivalent audience.’ This study addresses the question as to how translators deal with this dual audience. Do they stick to it or do they rather adapt the story more clearly to children? The corpus consists of the original Danish text and fourteen translations and adaptations in six languages. The research focuses on the implied dual audience as it is given shape in source and target texts on the phonological, lexical-semantic, syntactic and pragmatic levels. The first part of the article investigates how substitutions, omissions and rearrangements might change the dual orientation of the text. The second part deals with the additions and examines how they influence the divertive, creative, emotional and educative function of the text.